Milk production of dairy ewes fed in stall or grazing green barley or ryegrass pastures - Yagoubi Y.; Habachi F.; Smeti S.; Mekki I.; Atti N. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Sheep dairy production depends on many factors such as rearing system, the nature of forage and the supplementation level. Hence, the objective of this study was the evaluation of the milk production and quality of Sicilo-Sarde ewes raised in feedlot or grazing green barley and perennial ryegrass. Sheep were divided into 4 groups. The stall (ST) group received ad-libitum hay and silage with 500g of concentrate. Two groups were grazed on green barley (B) and one on rye-grass (RG). Grazing was managed rotationally with a stocking rate of 25 ewes/ha. The RG group and one of the B groups (B-CC) were supplemented with 300g concentrate; the last group did not receive concentrate (B-C0). The average biomass production was 3.43 and 2.03 tons of dry matter (DM) per hectare for green barley and ryegrass, respectively. Total and daily milk production of ewes was significantly (P <0.001) higher for pasture groups than for the ST group. The daily milk yield was 349, 599, 647 and 592 ml/ewe, for ST, B-C0, B-CC and RG, respectively. Milk fat and protein content were significantly higher for ST than for the grazing groups (P <0.001), while fat and protein yields were higher for grazing groups than for the ST (47 vs. 32 g/d, respectively). As a conclusion, grazing improves milk production with a lower concentrate supply.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)